Analysis of Occupational Health, and Safety (K3) in the Workshop Area Using the HIRA and 5S Methods at PT. Ravana Jaya - Alfin Nurissa'adah; Elly Ismiyah; Akhmad Wasiur Rizqi (Indonesian Mechanical Electrical and Industrial Research Society (IMEIRS), 2022)
PT. Ravana Jaya is an industrial company engaged in the construction of building frames. The problem that occurs in this company is the high rate of work accidents. The purpose of using the HIRA and 5S methods in this study is to identify potential hazards that exist in companies with a 5S cultural approach to minimize work accidents in the workshop. The results of the risk assessment of this study contained 31 hazards as follows: 6 extreme risk categories, 15 high-risk categories, 4 moderate risk categories, and 6 low-risk categories. The results of the 5S proposal at each workstation, in a nutshell, workers must always clean the work area from garbage or material remnants, tidy up and be able to sort out materials of type and type to be used in one area, routinely perform machine maintenance and check the machines used, know SOPs that must be run from the tools or machines that will be used, workers must use complete PPE following the needs at each workstation. PT. Ravana Jaya adalah perusahaan industri yang bergerak di bidang kontruksi pembuatan kerangka bangunan. Permasalahan yang terjadi pada perusahaan ini adalah tingginya tingkat kecelakaan kerja. Tujuan menggunakan metode HIRA dan 5S pada penelitian ini untuk mengidentifikasi potensi bahaya yang ada di perusahaan dengan pendekatan budaya 5S untuk meminimalisir kecelakaan kerja di area workshop. Hasil risk assessment penelitian ini terdapat 31 identifikasi bahaya sebagai berikut: 6 kategori extreme risk, 15 kategori high risk, 4 kategori medium risk dan 6 kategori low risk. Hasil usulan 5S pada setiap stasiun kerja secara ringkas menunjukan pekerja harus selalu membersihkan area kerja dari sampah atau sisa – sisa dari material, merapikan dan dapat memilah material dari jenis maupun yang akan digunakan dalam satu area, rutin dalam melakukan perawatan mesin dan pengecekan mesin sebelum digunakan, mengetahui SOP yang harus dijalankan dari alat atau mesin yang akan digunakan, pekerja harus menggunakan APD dengan lengkap yang sesuai dengan kebutuhan di stasiun kerja masing – masing.